Identification and antibiotic resistance of pseudomonas sp. / Noramalina Ab Hamed - Ab Hamed, Noramalina (Faculty of Applied Sciences, 2017)
Pseudomonas sp. is one of the opportunistic pathogens and human pathogens. The evolution and spread of antibiotic resistance has been identified as a global threat to human, animal, and environmental health. The aims of this study were to identify the Pseudomonas sp. by using polymerase chain reaction (PCR) method and to identify the antibiotics resistance of Pseudomonas sp. In this study, ten types of antibiotics were used and differentiated by their mechanisms of action. The antibiotics used are aminoglycosides' amikacin and streptomycin, cephalosporin's cephalotine and ceftazidime, fluoroquinolones' ciprofloxacin and norfloxacin, macrolide' s erythromycin and clindamycin, and penicillin's penicillin and ampicillin. Next, Pseudomonas sp. was identified by using PCR method. For the identification of Pseudomonas sp., the bacteria showed bands with 251 bp sizes and parallel with the positive control of Pseudomonas sp. pure culture. While for the antibiotics resistance test, disc diffusion method was used. The bacteria are resistant to streptomycin, cephalotine, erythromycin, clindamycin, penicillin, and ampicillin. In contrast, the bacteria are susceptible to amikacin, ceftazidime, ciprofloxacin and norfloxacin. The MAR index shows high value, which are between 0.5 and 0.6. Thus, Pseudomonas sp. is categorized under highly risk bacteria.